Exploring HPV vaccination policy and payer strategies for opportunities to improve uptake in safety-net settings - Kylie Sloan; Michelle Shin; Lawrence A. Palinkas; Shawna V. Hudson; Benjamin F. Crabtree; Joel C. Cantor; Jennifer Tsui (Frontiers Media S.A., 2023)
IntroductionWe explored priorities and perspectives on health policy and payer strategies for improving HPV vaccination rates in safety-net settings in the United States.MethodsWe conducted qualitative interviews with policy and payer representatives in the greater Los Angeles region and state of New Jersey between December 2020 and January 2022. Practice Change Model domains guided data collection, thematic analysis, and interpretation.ResultsFive themes emerged from interviews with 11 policy and 8 payer participants, including: (1) payer representatives not prioritizing HPV vaccination specifically in incentive-driven clinic metrics; (2) policy representatives noting region-specific HPV vaccine policy options; (3) inconsistent motivation across policy/payer groups to improve HPV vaccination; (4) targeting of HPV vaccination in quality improvement initiatives suggested across policy/payer groups; and (5) COVID-19 pandemic viewed as both barrier and opportunity for HPV vaccination improvement across policy/payer groups.DiscussionOur findings indicate opportunities for incorporating policy and payer perspectives into HPV vaccine improvement processes. We identified a need to translate effective policy and payer strategies, such as pay-for-performance programs, to improve HPV vaccination within safety-net settings. COVID-19 vaccination strategies and community efforts create potential policy windows for expanding HPV vaccine awareness and access.